PEMANFAATAN LIMBAH SAGU SEBAGAI BAHAN PAPAN PARTIKEL - Suwandi Kliwon; Rozak Memed (Jurnal Penelitian Hasil Hutan, 1989)
The  experiment  result  of  using  sago  waste  for particleboard   is reported  in this paper.   The experiment  covers  the process   of   making   particleboard    with   several  raw  material  compositions    and   testing   their  physical   and  mechanical properties.   The  particleboard   is bonded   with  urea formaldehyde    resin with  the dimension   of  30 cm x  30 cm  x  1,5 cm,The  results  indicate  that  most  of  the physical  properties  of particleboard   meet  Indonesian  or FAO standards,  while many   of  mechanical  properties   do  not  meet  those  standards.  Veneer   lamination   improves  the  bending  strength  and  the addition   of  sago  bark  do  not  improve  physical   and  mechanical  properties   of  particleboard.